ECOLOGICAL CULTURE IN THE CONTEXT OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT: THE UKRAINIAN REALITIES AND PROSPECTS - Maryna Bratitsel (Культура і мистецтво у сучасному світі, 2020)
The purpose of the article is to identify the features of the development of ecological culture in the modern Ukrainian society according to the concept of the sustainable development. The research methodology is based on the use of the axiological method, which provided the harmonization of knowledge, moral and spiritual development of a person, and contributed to the identification of a personal perception of nature as selfworth and a man. The system approach helped to describe an object as a systematic whole in terms of its structure, elements, purpose, and functions. The historical and logical method contributed to the study of dynamic transformations of relationships in the system “man-nature-society”; according to the sociocultural ecological culture is a type of world-view and a way of mastering social and cultural experience in accordance with the principle of co-evolution. The scientific novelty lies in the identification of trends in the ecological innovation culture as a part of the sustainable development concept and current environmental initiatives of domestic entrepreneurs in the process of modernization of the Ukrainian society. Conclusions. The study has shown that environmental sustainability has become an integral part of business practices in all areas of the human activity. It includes: the improvement of living standards by protecting human health, preserving the environment, efficient use of resources and ensuring long-term economic competitiveness. Thus, the definition of sustainability focuses on four areas: education, process, community participation, and future conditions. Though, the concept of sustainable development has not become widespread in the Ukrainian practice, there are several hundred public environmental organizations, associations and movements at the state and regional levels. Ecological guidelines of upbringing, culture and education based on the ecological consciousness and morality by rethinking the environmental safety in the material and moral spheres become expedient in the context of the prospects of the development. It has been identified that the main task of the Ukrainian society is to increase the demand for the ecological innovations and the current trend – the program of supporting sustainable development as the best way for a manufacturer to demonstrate its care and attention to consumers. It has been defined that the main trend in the development of the ecological culture in the context of the European integration processes should be the formation of a model of ecoculture based on the moral and spiritual dominant of the world perception in the public consciousness, a change in the sociocultural mentality and responsible attitude to the environmental issues.